Degradation of selected agrochemicals by the white rot fungus Trametes versicolor - Mir Tutusaus, Josep Anton (2014)
Use of agrochemicals is a worldwide practice that exerts an important effect on the environment; therefore the search of approaches for the elimination of such pollutants should be encouraged. The degradation of the insecticides imiprothrin (IP) and cypermethrin (CP), the insecticide/nematicide carbofuran (CBF) and the antibiotic of agricultural use oxytetracycline (OTC) were assayed with the white rot fungus Trametes versicolor. Experiments with fungal pellets demonstrated extensive degradation of the four tested agrochemicals, at rates that followed the pattern IP > OTC > CP > CBF. In vitro assays with laccase-mediator systems showed that this extracellular enzyme participates in the transformation of IP but not in the cases of CBF and OTC. On the other hand, in vivo studies with inhibitors of cytochrome P450 revealed that this intracellular system plays an important role in the degradation of IP, OTC and CBF, but not for CP. The compounds 3-(2,2-dichlorovinyl)-2,2-dimethylcyclopropane carboxylic acid (DCCA) and 3-phenoxybenzoic acid (PBA) were detected as transformation products of CP, as a result of the breakdown of the molecule. Meanwhile, 3-hydroxycarbofuran was detected as a transformation product of CBF; this metabolite tended to accumulate during the process, nonetheless, the toxicity of the system was effectively reduced. Simultaneous degradation of CBF and OTC showed a reduction in toxicity; similarly, when successive additions of OTC were done during the slower degradation of CBF, the fungal pellets were able to degrade both compounds. The simultaneous degradation of the four compounds successfully took place with minimal inhibition of fungal activity and resulted in the reduction of the global toxicity, thus supporting the potential use of T. versicolor for the treatment of diverse agrochemicals.